Pre-existing CD4 T cell help boosts antibody responses but has limited impact on germinal center, antigen-specific B cell frequencies after influenza infection - Besavilla, Danica F.; Reusch, Laura; Enriquez, Josue; Schön, Karin; Angeletti, Davide (Frontiers in Immunology, 2023)
Influenza virus is a persistent burden on global health, with seasonal vaccines providing incomplete protection. CD4+ T cell help shapes B cell and antibody responses, however, the selectivity of help and the effect on various antigen-specific B cell populations have not been fully elucidated. Here, we studied the specificity, selectivity, and influence of nucleoprotein (NP) CD4+ T cells on the magnitude and quality of hemagglutinin (HA) and NP-specific B cells and antibody responses. We identified immunodominant peptides and showed that peptide immunization was sufficient to induce CD4+ cells with Th1 and Tfh phenotypes. Surprisingly, while preexisting CD4+ T cells enhanced the influx of total germinal center (GC) B cells in the mediastinal lymph node after infection, this was not reflected by an increase in the frequency of antigen-specific cells within the GC. Furthermore, we demonstrated that NP-specific help was able to accelerate the kinetics and magnitude of the Ab response for NP but not for HA. Overall, our results show that pre-existing CD4+ T cells provide strong cognate help during immunization or infection to enhance Ab production but not antigen-specific GC or memory B cells